Helicobacter pylori adhesin HopQ disrupts trans dimerization in human CEACAMs. (1st June 2018) - Moonens, Kristof; Hamway, Youssef; Neddermann, Matthias; Reschke, Marc; Tegtmeyer, Nicole; Kruse, Tobias; Kammerer, Robert; Mejías‐Luque, Raquel; Singer, Bernhard B; Backert, Steffen; Gerhard, Markus; Remaut, Han
Abstract: The human gastric pathogen Helicobacter pylori is a major causative agent of gastritis, peptic ulcer disease, and gastric cancer. As part of its adhesive lifestyle, the bacterium targets members of the carcinoembryonic antigen‐related cell adhesion molecule (CEACAM) family by the conserved outer membrane adhesin HopQ. The HopQ–CEACAM1 interaction is associated with inflammatory responses and enables the intracellular delivery and phosphorylation of the CagA oncoprotein via a yet unknown mechanism. Here, we generated crystal structures of HopQ isotypes I and II bound to the N‐terminal domain of human CEACAM1 (C1ND) and elucidated the structural basis of H. pylori specificity toward human CEACAM receptors. Both HopQ alleles target the β‐strands G, F, and C of C1ND, which form the trans dimerization interface in homo‐ and heterophilic CEACAM interactions. Using SAXS, we show that the HopQ ectodomain is sufficient to induce C1ND monomerization and thus providing H. pylori a route to influence CEACAM‐mediated cell adherence and signaling events. Synopsis: Binding of the H. pylori HopQ adhesin to CEACAM receptors allows delivery of the CagA oncoprotein and hijacking of host cell signaling. Crystal structures and funcional analyses of type I and II HopQ bound to human CEACAM1 provide mechanistic insight into this virulence‐enhancing host‐pathogen interaction. HopQ binds the CEACAM trans ‐dimerization interface and leads to CEACAM monomerization. HopQ binds CEACAM1 via an induced fit in disulfide‐clasped interaction loops. CEACAM‐mediated signalling is not required for HopQ‐dependent CagA translocation and phosphorylation. The HopQ type I and II alleles show strain‐dependent CEACAM specificities. Abstract : Crystal structures of HopQ and functional analyses reveal the mechanism by which H. pylori HopQ interacts with human CEACAM to inject the oncoprotein CagA into host cells.